Simulation of low-frequency PWR neutron flux fluctuations. (November 2019) - Viebach, M.; Lange, C.; Bernt, N.; Seidl, M.; Hennig, D.; Hurtado, A.
Abstract: Several KWU type PWRs have experienced an unexplained cycle-by-cycle change of neutron flux fluctuation amplitudes. The phenomenon is a matter of ongoing research. It has drawn attention to long-known but also not entirely understood long-range correlations in the time-dependent neutron flux signals. A sufficient understanding of these correlations and the corresponding phase relations is needed to explain the cycle-by-cycle change of the neutron flux fluctuation amplitudes. As previous research has shown, coherent deflection of a large number of fuel assemblies could contribute to the observed fluctuation patterns. Therefore, the contribution at hand investigates the effect of a quasi-coherent deflection of all fuel assemblies on the neutron flux fluctuations. The considered model assumes that this behavior has an impact in the reflector only. This impact is quantified via CASMO5 calculations and subsequent DYN3D simulations. In addition to the reflector perturbation, fluctuations of the inlet temperature distribution are superimposed. The simulation results are discussed along with selected data of measured neutron flux fluctuations. On the one hand, it is verified that coherent fuel assembly deflections can contribute to the measured neutron flux patterns as the simulations reproduce the main characteristics of the relevant neutron flux fluctuation phenomena. On the other hand, it turns out that the perturbations in the reflector may not be the only path of action relevant for the observed correlations. Approaches for future research are given.